2008
DOI: 10.1111/j.1525-1438.2007.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

The attitude and knowledge of cervical cancer by Cameroonian women; a clinical survey conducted in Maroua, the capital of Far North Province of Cameroon

Abstract: This study was conducted to assess the knowledge, attitudes, and assumption of cervical cancer by women living in Maroua, the capital of the Far North Province of Cameroon. In a 1-month period, 171 women were surveyed as to their socioeconomic status, sexual habits, prior knowledge of cervical cancer, its prevention, and their attitudes toward cervical cancer. Of 171 women, 48 (28%) had prior knowledge of cervical cancer; they were classified as the "aware group" compared with 123 of 171 (72%) women who were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
4
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 22 publications
9
60
4
4
Order By: Relevance
“…About half of the women had "fair" knowledge while, 40.7%, had "poor" knowledge ( Table 1). This appears to be a common problem in other parts of the country like in Maroua [9] and other sub Saharan countries where similar findings were documented [11] [12].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…About half of the women had "fair" knowledge while, 40.7%, had "poor" knowledge ( Table 1). This appears to be a common problem in other parts of the country like in Maroua [9] and other sub Saharan countries where similar findings were documented [11] [12].…”
Section: Discussionsupporting
confidence: 64%
“…The younger age group is also less likely to be screened if the U.S. Preventive Services Task Force recommendation statement of screening women as from 21 years is respected by health care providers [8]. However, some researchers recommend screening to be carried out for sexually active women irrespective of age [9]. The majority of women who were screened in this study were above 40 years.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…62.7% had heard of cervical cancer in the present study. This proportion is higher than that reported in a Nigerian study [11], though comparable to a study in Cameroon [12] and slightly lower than that reported in an Ethiopian study [13]. Only 39.1% (n = 174) believed that cervical cancer can be prevented and indeed only a few had been screened.…”
Section: Discussioncontrasting
confidence: 53%
“…Bu konuda yapılan birçok araştırma sonuçlarına göre; kadınların büyük bir çoğunluğunun serviks kanseri hakkında bilgilerinin olmadığı ve serviks kanseri konusunda bilgi alan kadınların ön teste göre son testte bilgilerinin arttığı belirtilmiştir [10][11][12][13] . Büyük stres ve sorun yaratan serviks kanserine yakalanmamak veya çok erken dö-nemde teşhis edilip tedavisini mümkün kılmak ancak kadınların bu konuda bilgilendirilmeleri ve eğitilmele-ri ile sağlanabilir 14 .…”
Section: Introductionunclassified